2023
DOI: 10.1002/tpg2.20300
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of spike and kernel traits in the U.S. hard winter wheat

Abstract: A better understanding of the genetic control of spike and kernel traits that have higher heritability can help in the development of high‐yielding wheat varieties. Here, we identified the marker‐trait associations (MTAs) for various spike‐ and kernel‐related traits in winter wheat (Triticum aestivum L.) through genome‐wide association studies (GWAS). An association mapping panel comprising 297 hard winter wheat accessions from the U.S. Great Plains was evaluated for eight spike‐ and kernel‐related traits in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 152 publications
1
4
0
Order By: Relevance
“…Similarly, four MTAs were identified on 3D, 2D, 3A, and 2B for TKW. MTAs for TKW on the same chromosomes in different mapping populations were also identified in earlier reports on 1B [ 27 ], 2B [ 28 , 91 ], 2D [ 25 , 80 , 91 , 92 , 93 ], 3A [ 88 , 93 , 94 , 95 ] at different chromosomal locations. Cabral et al [ 27 ] identified a QTL, i.e., QGwt.crc-2B-2 , on the 2B chromosome, located at a confidence interval of 92.9–96.0 cM, which was similar to the MTA ( AX-95194336 ) detected in the current study on the same chromosome at 96.2 Mb.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, four MTAs were identified on 3D, 2D, 3A, and 2B for TKW. MTAs for TKW on the same chromosomes in different mapping populations were also identified in earlier reports on 1B [ 27 ], 2B [ 28 , 91 ], 2D [ 25 , 80 , 91 , 92 , 93 ], 3A [ 88 , 93 , 94 , 95 ] at different chromosomal locations. Cabral et al [ 27 ] identified a QTL, i.e., QGwt.crc-2B-2 , on the 2B chromosome, located at a confidence interval of 92.9–96.0 cM, which was similar to the MTA ( AX-95194336 ) detected in the current study on the same chromosome at 96.2 Mb.…”
Section: Discussionsupporting
confidence: 77%
“…GWAS has been successfully utilized in identifying the significant MTAs associated with drought tolerance at various developmental stages ( Gill et al., 2022 ; Tanin et al., 2022 ; Halder et al., 2023 ). Most of these studies were conducted at reproductive stages.…”
Section: Discussionmentioning
confidence: 99%
“…A collection of winter wheat from Central Asia was compiled, including accessions from Kazakhstan (52), Kyrgyzstan (27), Tajikistan (9), and Uzbekistan (27). The samples from Central Asia, along with accessions from other parts of the world, were united to form the CAWBIN winter wheat collection, consisting of 277 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, grain productivity in the U.K. was 7.8 t/ha per year during 2021-2022 [4]. It is well known that grain yield is a complex trait and is associated with main components such as the number of productive spikes, spike length, number of spikelets per spike, number of kernels per spike, kernel size, and thousand-kernel weight [9]. The performance of these quantitative components is affected not only by environmental factors but also by genotype and is controlled by multiple quantitative trait loci (QTLs) located in different parts of the genome [10,11].…”
Section: Introductionmentioning
confidence: 99%